Correlation of Serum Nitric Oxide, High Sensitivity C-reactive Protein and Lipid Parameters in Diabetics with and without Coronary Artery Disease - Kavitha M. M; J. G Ambekar; S. V Kashinakunti; Nilima Dongre (Journal of Krishna Institute of Medical Sciences University)
Background: Coronary Artery Disease (CAD) and Diabetes Mellitus (DM) top the list among noncommunicable diseases. Nitric Oxide (NO) preserves normal vascular physiology. Uncoupling of endothelial nitric oxide synthase enzyme occurs in the blood vessels of diabetics leading to endothelial dysfunction and excessive production of superoxide anion causing decreased bioavailability of NO. Aim and Objectives: To assess the serum NO levels, highsensitive C-reactive Protein (hsCRP), lipid parameters and their association with CAD in diabetics. Material and Methods: The study comprises total 195 participants. There are three groups, each group consist of 65 participants. Three groups were diabetes with CAD, diabetes without CAD and control. NO assessed by modified Griess method. hsCRP by immunoturburdimetric method FBS and lipid parameters were analysed in fully automated analyzer. Results: There was a significant decrease in NO levels and significant increase in hsCRP levels in diabetes without CAD and diabetes with CAD patients compared to controls. NO showed negative correlation with Fasting Blood Sugar (FBS) and hsCRP in DM without CAD patients. NO showed negative correlation with DBP in DM with CAD patients. NO showed negative correlation with HbA1c in both the groups. Conclusion: The study concludes that estimation of NO and hsCRP along with lipid profile,help in early detection of endothelial dysfunction in diabetese patients. Reduced NO and increased hsCRP levels in diabetese patients may be strong indicator of coronary artery disease.